Fusarium Fungi and Mycotoxins in Bee Pollen Collected in Lithuania - Jolanta Sinkevičienė; Živilė Tarasevičienė; Vytautas Tamutis (Applied Sciences, 2023)
This paper presents the results of a study which was aimed at determining the concentration of Fusarium fungi and their mycotoxins in fresh bee pollen, stored for different periods. The analysed parameters included palynological analysis, moisture content, fungal counts, identification and toxigenic profiles. In this study, 45 bee pollen samples collected from the same apiary families were investigated. Palynological analysis determined six plant families, among which Brassicaceae prevailed. The number of detected isolates in the bee pollen during the study period ranged from 3.5 × 103 to 9.1 × 104 cfu g−1. During the study, the most prevalent fungal genera of Alternaria, Cladosporium and Yeasts were found in fresh bee pollen. The significantly highest amounts of fungal colonies were determined after 3 days of storage of undried pollen. Fusarium fungal genera were detected in 46% of all studied samples, with levels ranging from 101 cfu g−1. After 3 days of storage, the most significant Fusarium spp. increase (17.03%) was detected. F. graminearum and F. sporotrichioides prevailed during the whole period of the study. The highest concentrations of mycotoxins ZEN (280 µg kg−1) and DON (120 µg kg−1) were found after 3 days of pollen storage. The results of the present study report the importance of microbiological and mycotoxicological analyses in monitoring bee pollen from the initial stages of its production process.